Determinants of managerial preventive actions in relation to common mental disorders at work. (13th November 2019) - van de Voort, I W H; De Rijk, A; Hensing, G; Bertilsson, M
Abstract: Background: Managers may prevent Common Mental Disorders (CMDs) among their subordinates due to their authority to influence the work environment. Yet, their perspective has received only limited attention in research. This study aims to increase managers' capacity to contribute to the prevention of CMDs by exploring the determinants of two managerial preventive actions: 'reviewing assignments and the work situation' (MPA-review) and 'taking initiative to talk about depression and anxiety at work' (MPA-talk). Methods: An online survey was sent to 4, 737 Swedish managers, aged 20-65 years (71% participated, n = 3, 358) in 2017, of which 2, 921 were included as they answered the MPA-items. Ten possible determinants of MPAs, comprising person-, work-, and competence-related characteristics of managers were related to performing MPAs (yes or no). Bivariate and multivariate binary logistic regression was performed to test associations (OR with 95% CI) between each determinant and MPAs. We have adjusted for experience-related characteristics of managers and company size. Results: 50% of managers initiated MPA-review and 57% MPA-talk. Managers had a higher odds to initiate respectively MPA-review and MPA-talk when being female (OR 1.42, 95% CI 1.17-1.73; OR 1.33, 95% CI 1.08-1.64), working in organizations offering lectures on CMDs (OR 1.36, 95% CI 1.01-1.83; OR 1.84, 95% CI 1.30-2.60) or stress counselling (OR 1.79, 95% 1.46-2.20; OR 1.53, 95% CI 1.22-1.91), having responsibility for the work environment (OR 1.42, 95% CI 1.15-1.74; OR 1.44, 95% CI 1.16-1.79), or having had received training on CMDs (OR 1.56, 95% CI 1.27-1.93; OR 1.61, 95% CI 1.28-2.03). Conclusions: Managers report taking more actions to prevent CMDs in their workforce when they are female, have received training on CMDs or work in organisations where CMD preventive measures have been implemented. Key messages: Organizations could invest in company-wide preventive measures and training to enable MPAs. Managerial education should include information on CMDs in order to improve managers' preventive capacity.